Lumbopelvic Muscle Changes Following Long-Duration Spaceflight - McNamara, Kyle P.; Greene, Katelyn A.; Moore, Austin M.; Lenchik, Leon; Weaver, Ashley A. (Frontiers in Physiology, 2019)
Long-duration spaceflight has been shown to negatively affect the lumbopelvic muscles of crewmembers. Through analysis of computed tomography scans of crewmembers on 4- to 6-month missions equipped with the interim Resistive Exercise Device, the structural deterioration of the psoas, quadratus lumborum, and paraspinal muscles was assessed. Computed tomography scans of 16 crewmembers were collected before and after long-duration spaceflight. The volume and attenuation of lumbar musculature at the L2 vertebral level was measured. Percent changes in the lumbopelvic muscle volume and attenuation (indicative of myosteatosis, or intermuscular fat infiltration) following spaceflight were calculated. Due to historical studies demonstrating only decreases in the muscles assessed, a one-sample t test was performed to determine if these decreases persist in more recent flight conditions. Crewmembers on interim Resistive Exercise Device-equipped missions experienced an average 9.5% decrease in volume and 6.0% decrease in attenuation in the quadratus lumborum muscles, and an average 5.3% decrease in volume and 5.3% decrease in attenuation in the paraspinal muscles. Crewmembers experienced no significant changes in psoas muscle volume or attenuation. No significant changes in intermuscular adipose tissue volume or attenuation were found in any muscles. Long-duration spaceflight was associated with preservation of psoas muscle volume and attenuation, and significant decreases in quadratus lumborum and paraspinal muscle volume and attenuation.